UJI TOKSISITAS AKUT EKSTRAK ETANOL 70% KULIT PISANG KEPOK KUNING (Musa paradisiaca L.) TERHADAP LARVA UDANG (Artemia salina Leach) MENGGUNAKAN METODE Brine Shrimp Lethality Test (BSLT) - Hasriyani, Hasriyani; Putri Rahmawati, Riana; Putri Utami, Meira (Yayasan Nusantara Hasana Berdikari, 2025)
Yellow kepok banana is a horticultural plant native to Indonesia in Southeast Asia, which is used as an antimicrobial, antihypertensive, antiallergic, antioxidant, antianalgesic, diuretic, hypolipidemic and vasodilator. Yellow kepok banana peel is a waste of kepok banana which contains high antioxidant compounds such as phenol, catecholamide, carotene and flavonoids, polyphenols, vitamin C, and tannins. Method: Experimental research design, 180 Artemia Shrimp Larvae were divided into 5 concentration groups consisting of 10 shrimp larvae with 3 replications of concentration groups, namely 250, 500, 750, 1,000 ppm. Results: Phytochemical screening of 70% ethanol extract of yellow kepok banana peel contains active compounds of alkaloids, flavonoids, saponins, and tannins. Observations for 24 hours, at a concentration of 250 ppm there was a percentage of death of 63%, at a concentration of 500 ppm of 73%, at a concentration of 750 ppm of 87% and a concentration of 1000 ppm of 97%. The LC50 value obtained was 38.899 ppm. So the highest dose is 1,000 ppm and it can be stated that the yellow banana peel extract in this study was highly toxic to Artemia salina larvae test animals so that it can be used as an anti-cancer. Conclusion: Ethanol extract of 70% yellow banana peel has the potential for acute toxicity to Artemia Shrimp Larvae using the (BSLT) method because the LC50 value was <50 µg/ml.